Interaction Between Lactic Acid Bacteria and Acetic Acid Bacteria in Sichuan Bran Vinegar: Impact on Their Growth and Metabolites - Jianlong Li; Jie Wu; Meiling Tu; Xue Xiao; Kaidi Hu; Qin Li; Ning Zhao; Aiping Liu; Xiaolin Ao; Xinjie Hu; Shuliang Liu (Foods)
Microbial interactions are essential for maintaining the stability and functionality of microbiota in fermented foods. In this study, representative strains of predominant lactic acid bacteria and acetic acid bacteria in Sichuan bran vinegar were selected, and their interactions in a simulated solid-state fermentation system were investigated. The results reveal that the biomass of A. pasteurianus LA10 significantly increased in both the co-culture and the pure culture, whereas the biomass of L. amylovorus LL34 in the co-culture (6.44 ± 0.30 lg CFU/g) was significantly lower than that in the pure culture (7.28 ± 0.30 lg CFU/g) (p < 0.05), indicating a partially harmful symbiosis between these two strains. The metabolic analysis shows that total acid (21.82 mg/g) and acetic acid (9.53 mg/g) contents in the co-culture were lower than those in the pure culture of LA10, suggesting that LL34 inhibited the acid-producing activity of LA10 to some extent. The interaction between the two bacteria also influenced the production of volatile compounds and non-volatile compounds, as revealed by GC-MS and untargeted UHPLC-MS/MS, respectively. Significant enrichment of acid and amino acid metabolism pathways was observed in the co-culture, revealing the impact of bacterial interactions on flavor development. This study provides valuable insights into the advancement of vinegar brewing technology.